Unequal Hiring Wages and Their Impact on the Gender Pay Gap - Tho Pham; Daniel Schaefer; Carl Singleton (Institute of Labor Economics (IZA), 2024)
National payroll earnings data reveal that men are generally paid more than women when they enter firms. Although this hiring wage gap has narrowed over the past two decades, it still accounts for over half of the overall gender pay gap in Great Britain. Even when firms hire men and women into the same specific occupation at roughly the same time, and accounting for previous work experience, there remains an unexplained hiring wage gap within jobs that favours men by 2.6%. These findings suggest that gender pay gap reporting laws that focus exclusively on the overall gaps within employers miss an important margin. Mandating employers to additionally disclose their wage gaps among newly hired workers could be highly informative.
Keywords: J16; J31; J70; 330; gender segregation; occupation-specific wages; employer-employee data